Effectiveness Of Stestmap On Facilitating Significance Test Selection - Tang, Howe Eng; Lau, Ung Hua; Foo, Kien Kheng; Liew, Chin Ying; Chang, Robin Yee Hui; Ling, Teck Yee (Universiti Malaysia Sarawak, 2009)
In the hypothesis testing process, one of the difficult steps was in determining the appropriate significance test 10 use. Any misstep in the selection process could cause the users to come to the wrong conclusion. This study aimed to evaluate the effectiveness of STestMAP to help in the selection ofthe significance test. The study was quantitative in nature. Three instruments, which consisted of prior knowledge test, pre-test and post-test were adopted and administered. Data collection was carried out through paper-and-pencil tests. Quantitative (descriptive and inferential analysis) data analysis techniques were utilized. In Malaysia, a random sample of49 respondents from two public universities in Sarawak was chosen. The Wilcoxon Signed Rank Test showed that there was a statistically significant difference in pre-test and post-test for the control group, Z=-3.978, p=0.001 as well asfor the experimental group, Z=-4.275, p=0.001. In comparing the scores between the experimental and control group, however, the test indicated insignificant difference, Z=-0.142, p=0.887.111 Singapore, 29 respondents were selected on a voluntary basis from one of the public universities. Paired t-Test showed that there was a significant gain in the pre and post-tests (t= 7.678, p=0.001). For both Malaysia and Singapore, the analysis on the Cumulative Grade Point Average (CGPA) revealed statistical significant differences for certain group comparisons.